1995
DOI: 10.1111/j.1346-8138.1995.tb03426.x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Survey from 1982 to 1991 of 49 Patients with Malignant Melanocytic Tumors

Abstract: We investigated the clinical characteristics and outcome of 49 patients with malignant melanoma: 17 with acral lentiginous melanoma; 14 with nodular melanoma, six with superficial spreading melanoma, one with lentigo maligna melanoma, eight with melanoma in situ, one with malignant blue nevus, and two with melanoma of unknown origin. Of the 41 patients without melanoma in situ, 34.1% were in stage I, 17.1% in stage II, and 48.8% in stage III. No patients had reached stage IV. All patients with stage I, II, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…At present, chemotherapy and immunotherapy do not have major roles in the treatment of PMME. Several authors have reported a therapeutic effect of DTIC for melanomas that originate in organs other than the esophagus 16,17 . DTIC, ACNU, VCR, and platinum analogs all have therapeutic activity in cutaneous melanoma, and combination therapy that often includes tamoxifen is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, chemotherapy and immunotherapy do not have major roles in the treatment of PMME. Several authors have reported a therapeutic effect of DTIC for melanomas that originate in organs other than the esophagus 16,17 . DTIC, ACNU, VCR, and platinum analogs all have therapeutic activity in cutaneous melanoma, and combination therapy that often includes tamoxifen is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported a therapeutic effect of DTIC for melanomas that originate in organs other than the esophagus. 16,17 DTIC, ACNU, VCR, and platinum analogs all have therapeutic activity in cutaneous melanoma, and combination therapy that often includes tamoxifen is currently under investigation. Recently, a new combination therapy that uses chemotherapeutic and biological agents, e.g., cisplatin, interleukin-2 and interferonalpha, was reported to be effective against metastatic melanoma with a response rate that exceeded 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of IFN‐β and systemic chemotherapy is expected to provide better prognosis in melanoma patients. Previously, adjuvant therapy with DAV was applied to the treatment of cutaneous melanomas . However, DAV‐feron therapy brought no significant improvement in either disease‐free survival rates or melanoma‐specific survival rates of patients with cutaneous melanomas .…”
Section: Discussionmentioning
confidence: 99%
“…In 1 case, when chemotherapy was given to a patient with metastatic melanoma in the first trimester, the infant developed microphthalmos and hypermetropia. 6 Although treatment with interferon alfa-2b appears beneficial, 7 we used DAV-feron because the risk for teratogenicity and abortion appears low during the second and third trimester. In 2 other cases of metastatic melanomas treated with che-motherapy during pregnancy, the children survived, but the mothers died shortly after delivery.…”
Section: Report Of a Casementioning
confidence: 99%